Pedagogika katolicka – znaczenie i aktualność w kontekście chaosu wartości (perspektywa polska) - Chałupniak, Radosław (Studia Pastoralne, 2026)
Education cannot be reduced to information and should guarantee to the students and their parents the freedom of making axiological decisions and solutions. The above mentioned right is confirmed by the right of parents to raise their children according to their own conceptions. In the contemporary chaos of values and principles of education the Catholic education remains a topical, interesting and important proposal for school.